Disrupted BMP-9 Signaling Impairs Pulmonary Vascular Integrity in Hepatopulmonary Syndrome - Robert, Fabien; Certain, Marie-Caroline; Baron, Audrey; Thuillet, Raphaël; Duhaut, Léa; Ottaviani, Mina; Chelgham, Mustapha Kamel; Normand, Corinne; Berrebeh, Nihel; Ricard, Nicolas; Furlan, Valerie; Desroches-Castan, Agnès; et al. (American journal of respiratory and critical care medicine, 2024)
Hepatopulmonary syndrome (HPS) is a severe complication of liver diseases characterized by abnormal dilation of pulmonary vessels, resulting in impaired oxygenation. Recent research highlights the pivotal role of liver-produced BMP-9 (bone morphogenetic protein-9) in maintaining pulmonary vascular integrity. This study aimed to investigate the involvement of BMP-9 in human and experimental HPS. Circulating BMP-9 levels were measured in 63 healthy control subjects and 203 patients with cirrhosis with or without HPS. Two animal models of portal hypertension were employed: common bile duct ligation with cirrhosis and long-term partial portal vein ligation without cirrhosis. Additionally, the therapeutic effect of low-dose BMP activator FK506 was investigated, and the pulmonary vascular phenotype of BMP-9-knockout rats was analyzed. Patients with HPS related to compensated cirrhosis exhibited lower levels of circulating BMP-9 compared with patients without HPS. Patients with severe cirrhosis exhibited consistently low levels of BMP-9. HPS characteristics were observed in animal models, including intrapulmonary vascular dilations and an increase in the alveolar-arterial gradient. HPS development in both rat models correlated with reduced intrahepatic BMP-9 expression, decreased circulating BMP-9 level and activity, and impaired pulmonary BMP-9 endothelial pathway. Daily treatment with FK506 for 2 weeks restored the BMP pathway in the lungs, alleviating intrapulmonary vascular dilations and improving gas exchange impairment. Furthermore, BMP-9-knockout rats displayed a pulmonary HPS phenotype, supporting its role in disease progression. The study findings suggest that portal hypertension-induced loss of BMP-9 signaling contributes to HPS development.